Nontraumatic headaches in the emergency department: identifying clinical associations and predictive warning signs of intracranial pathologies - Abdulaziz M. Alghamdi; Abdulkarim M. Alghamdi; Yousof Fahad Allarakia; Arwa S. Alghamdi; Abdulaziz S. Alrashid; Abdulwhab M. Alotaibi; Reem Addas; Ahmed I. Lary (Annals of Saudi Medicine)
BACKGROUND: Although headaches are common, only 3–21% are estimated to be secondary, with their causes ranging from non-alarming to life-threatening conditions. OBJECTIVES: Evaluate the associated factors and predictive warning signs of intracranial pathologies in patients presenting with nontraumatic headaches to the emergency document (ED). DESIGN: Retrospective chart review SETTINGS: Medical center in Jeddah PATIENTS AND METHODS: Data were collected from all patients who presented to the ED with nontraumatic headaches and underwent brain computed tomography (CT) scans from September 2021 to September 2022. MAIN OUTCOME MEASURES: The associated factors and predictive warning signs of intracranial pathologies. SAMPLE SIZE: 387 RESULTS: Sixty-seven (17.31%) patients had intracranial pathologies. The median (IQR) age of all patients was 49 (23) years and females constituted 61.8%. Patients with intracranial pathologies were significantly more likely to have severe headaches (59.7% vs. 33.7%, P<.001), to have compressing or sharp headaches (16.4% vs. 6.2%, P=.003), to have constant headaches (16.4% vs. 7.8%, P=.003), to be on chemo-therapy or radiotherapy (10.5% vs. 2.8%, P=.004), and to be smokers (13.4% vs. 6.2%, P=.042) than the other group. Multiple logistic regression of headache warning signs revealed that significant changes or progression in pattern, frequency, or severity of headache (OR: 3.2, CI: 1.5–6.6, P=.001), motor deficits, including abnormal reflexes (OR: 2.9, CI: 1.2–6.9, P=.011), personality changes, confusion, memory impairment, drowsiness, slurred speech or loss of consciousness (OR: 2.6, CI: 1.4–5.0, P=.002), and sudden onset of headache (OR: 1.9, CI: 1.0–3.6, P=.046) were predictive of intracranial pathologies. CONCLUSIONS: Our findings suggest that these four headache warning signs can help physicians predict intracranial pathologies and subsequently decide which patients should undergo brain imaging in non-traumatic headache cases. LIMITATIONS: Single-center study and retrospective design